Risk of Recurrent Seizure in First Ever Seizure in Elderly - Wangphonphatthanasiri, Khwanrat (Journal of The Department of Medical Services, 2021)
Background : There are some approach and treatment guidelines for first seizure generally used in all age groups. The risk of recurrent seizure is proved to be highly significant and reasonable to start antiepileptic medication after the second seizure. However, in elderly patients, the seizure etiology is commonly symptomatic causes therefore the risk of seizure recurrence could be different and possibly higher comparing to other age groups even in first seizure. In order to understand the risk of recurrent seizure in first seizure in the elderly, the specific study in old age patients with first seizure is required. Objectives : To determine the risk factors of seizure recurrence in elderly and the treatment response in short (within 2 years) and long term duration (from 3-5 years). Methods : Retrospective study of 149 patients who were older than 65 years and diagnosed of first seizure at Prasat Neurological Institute during January 1, 2007- December 31, 2017 was performed. Medical history, blood chemistry, routine electroencephalogram (EEG) and brain imaging (CT or MRI) were reviewed. We evaluated the risk factors of seizure recurrence and treatment response in short and long term duration. Results : We identified 149 patients who had first seizure after the age of 65 years. 76 patients (51.0%) of this patients had recurrent seizures. The common etiologies were remote symptomatic (n = 78, 52.3%) and unknown causes (n = 44, 29.5%) respectively. Only clinical semiology of focal with impaired awareness and epileptic discharge abnormality were statistically significant predictors in term of seizure recurrence. Most of patients were treated by monotherapy and seizure could be controlled within 2 years. Conclusions : Most of elderly patients with first seizure have evidence of cerebrovascular disease as seizure etiology. Focal with unawareness and epileptic discharge abnormality from EEG are significant predictors of seizure recurrence. Second seizure commonly recurs within 4 months. However, majority of the cases respond well to antiepileptic medication without serious adverse events.